2018
DOI: 10.1167/tvst.7.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Contrast Sensitivity Function Using the qCSF Method With 10 Digits

Abstract: PurposeThe Bayesian adaptive quick contrast sensitivity function (qCSF) method with a 10-letter identification task provides an efficient CSF assessment. However, large populations are unfamiliar with letters and cannot benefit from this test. To overcome the barrier, we conducted this study.MethodA new font for digits (0∼9) was created. The digits were then filtered with a raised cosine filter, rescaled to different sizes to cover spatial frequencies from 0.5 to 16 cycles per degree (cpd), and used as stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
(85 reference statements)
1
38
0
Order By: Relevance
“…The estimate of the variability of the qCSF measurements could be obtained by calculating the half-width of the 68.2% credible intervals (HWCI). 34 , 35 Finally, to compare the variability of the measured sensitivities of our low vision population with that of a control population, HWCI for single qCSF run of the study population were compared with the HWCI width of individuals with normal vision measured using the same device, but at a different viewing distance (4 m instead of 1 m) ( n = 17) (Lesmes LA, et al IOVS 2016;57(12):ARVO E-Abstract 5161). Calculating the width of the credible interval of the posterior distribution pt(τ) from a single qCSF run is an alternative method to estimate the variability of the measured sensitivity (the 68.2% HWCI for a Gaussian distribution is equal to the standard deviation of the distribution).…”
Section: Methodsmentioning
confidence: 99%
“…The estimate of the variability of the qCSF measurements could be obtained by calculating the half-width of the 68.2% credible intervals (HWCI). 34 , 35 Finally, to compare the variability of the measured sensitivities of our low vision population with that of a control population, HWCI for single qCSF run of the study population were compared with the HWCI width of individuals with normal vision measured using the same device, but at a different viewing distance (4 m instead of 1 m) ( n = 17) (Lesmes LA, et al IOVS 2016;57(12):ARVO E-Abstract 5161). Calculating the width of the credible interval of the posterior distribution pt(τ) from a single qCSF run is an alternative method to estimate the variability of the measured sensitivity (the 68.2% HWCI for a Gaussian distribution is equal to the standard deviation of the distribution).…”
Section: Methodsmentioning
confidence: 99%
“…In characterizing spatial vision, the area under the log contrast sensitivity function is often used as a summary metric (Applegate et al, 1998 , 2000 ; Oshika et al, 1999 , 2006 ; van Gaalen et al, 2009 ; Hou et al, 2010 ; Lesmes et al, 2010 ; Jia et al, 2014 ; Dorr et al, 2015 ; Zheng et al, 2018 ). Here, we used the volume under the surface of the VFM (VUSVFM) to provide a summary metric of the entire visual field.…”
Section: Simulationsmentioning
confidence: 99%
“…There is an added advantage that characters have distinct spatial structures and can be readily recognized without much effort. Indeed, a number of recent developments have shown that CSF tests with 10-alterantive forced choice tasks using either Sloan letters 24 or digits 25 are much more efficient than those with 2AFC grating tests. Because of the presence of multiple spatial channels in the visual system, 6 the contrast sensitivity function; that is, contrast sensitivity as a function of spatial frequency, measured with narrow-band stimuli provides a more comprehensive assessment of vision.…”
Section: Introductionmentioning
confidence: 99%
“…15,24,26 Many studies have used bandpass filtered letter or digit stimuli to assess the CSF. 24,25,27,28…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation